"Paedagogia Homiletica Viatorum".: A pedagogy of the road for African Christian preaching - Wepener, Cas (Stellenbosch theological journal, 2024)
The four movements of the "Lukan liturgy" on the road to Emmaus, specifically the gathering, word, table and sending, are used to develop route markers for a homiletical pedagogy of the road for Africa. An argument is advanced for a special kind of contact between lecturer and students that takes seriously a variety of epistemologies and ontologies; for prioritising listening to speaking; for a pedagogy that serves a postcolonial imagination; and lastly, for a teleological orientation that works with an anthropology of desire and preaching as a Christopraxis event.